Identification of Bacteria on Seblak Food around University of Jember Based on Microbiological Criteria of Processed Food - Rizka Maulidya Cahyani; Joko Waluyo; Mochammad Iqbal (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2020)
The quality of food that is good in bacteriological, chemical and physical must always be maintained in order to avoid diseases or health problems. Healthy and safe food is an important factor to improve the standard of public health. Seblak is a ready-to-eat Indonesian food which until now has never been carried out research about what kinds of bacteria in it. Seblak is a food made from raw crackers which is then deliberately soaked using hot water to have a chewy texture. This study aims to determine what types of bacteria are contained in seblak, through the process of isolation and identification in the macroscopic, microscopic and biochemical way. This study used 5 samples, which was repeated 5 times for each sample. Bacteria were isolated from the sample using spread plate techniques and observed by growing colonies on the plate. Each different colonies was observed microscopically through gram staining and endospore staining. To strengthen the data, biochemical tests were also carried out, biochemical tests that have been done in this study were the oxidase test, catalase test, and indole test. The results of the study showed that the bacteria that were found from the samples are in the genus of Bacillus sp. because they show the morphological characteristics of the colonies that form concentric circles, meanwhile, microscopic observations show morphological characteristics of cells in the form of gram-negative bacilli and have the endospores.